THE DEVELOPMENT OF KLUY - PEANG - OR FLUTE PLAYING SKILLS BY USING A PRACTICAL LEARNING PROCESS COMBINED WITH SKILL EXERCISES OF MATHAYOM SUKSA 2 STUDENTS AT SATING PHRA WITTHAYA SCHOOL, SATING PHRA DISTRICT, SONGKHLA PROVINCE - Phahulo, Woraphet; Boonprakarn, Kettawa; Thusaro, Chutima (Journal of MCU Nakhondhat, 2023)
The purposes of this research article are 1) to compare Kluy - Peang - Or flute practice skill by learning management with practical process combined with skill exercises during pre - learning and post - learning, 2) to study the satisfaction towards learning management of Kluy - Peang - Or flute practice skill by providing a practical process learning management together with a skill exercises using a quasi - experimental research method. The sample consisted of 36 Mathayom Suksa 2 students at Sathing Phra Witthaya School, Sathing Phra District, Songkhla Province. It was obtained by cluster random sampling using the classroom as a random unit. The tools used were the learning management 4 plan 12 hours, the Kluy - Peang - Or flute practice skill exercises, and the satisfaction questionnaire. Check the quality of the tools by assessing their suitability and found that they pass the criteria. The satisfaction questionnaire had an accuracy value of .67 - 1.00, a confidence value of .98, found that it passed the criteria. The data were analyzed by percentage, mean, standard deviation and t - test dependent. The results showed that 1) the Kluy - Peang - Or flute practice skills by learning management with practical process combined with skills exercises after learning were higher than before learning at the statistical significance level of .001. 2) the overall satisfaction towards Kluy - Peang - Or flute skill learning management with practical process and skill exercises was at the highest satisfaction level ( = 4.74, S.D. = 0.44), when considered individually, it was found that students were satisfied at the highest level, that is, satisfaction with learning activities that promote self - learning ( = 4.89, S.D.= 0.32), followed by students who liked to practice with real musical instruments ( = 4.86, S.D.= 0.35), students were enthusiastic about learning and were satisfied with learning to play the Kluy - Peang Or flute ( = 4.83, S.D.= 0.38)